Trouble walked in - Kupari, Mike (Baen, 2023)
"A search for a missing woman exposes a conspiracy that could threaten an entire planet. Cassandra Blake, an employee for the Ascension Planetary Holdings Group - the largest and most powerful corporation in Nova Columbia - has gone missing. And her sister wants to know why. When questions need answering on Nova Columbia, Detective Ezekiel "Easy" Novak is the man folks turn to. He gets results -- one way or another. But what begins as a routine missing person case quickly turns into something much bigger and more sinister, with implications that could affect the entire planet. It seems Cassandra wasn't just investigating her employer. She had uncovered a secret effort to excavate and exploit an ancient alien artifact known only as The Seraph. Soon, Easy finds himself trying to unravel a conspiracy that may implicate not only Ascension, but the cultlike Cosmic Ontological Foundation-and the highest echelons of the Terran Confederation itself"--